Nonlinear Super Integrable Couplings of Super Dirac Hierarchy and Its Super Hamiltonian Structures - 尤福财 (Communications in theoretical physics, 2012)
We construct nonlinear super integrable couplings of the super integrable Dirac hierarchy based on an enlarged matrix Lie superalgebra. Then its super Hamiltonian structure is furnished by super trace identity. As its reduction, we gain the nonlinear integrable couplings of the classical integrable Dirac hierarchy.